Transitioning Out of an Urban Domestic Violence Emergency Shelter: Voices of Survivors. (September 2021) - Stylianou, Amanda M.; Hoge, Gretchen L.
Domestic violence (DV) shelters play a critical role for survivors and lead to a range of positive outcomes for families. However, transitioning in and out of temporary homelessness involves a range of stressors and research indicates that survivors transitioning out of DV shelters continue to have a multitude of needs. The focus of this study is to utilize an empowerment-based feminist lens to understand the process of transitioning out of a DV emergency shelter among 27 shelter residents in urban emergency shelters. Participants described the successes, challenges, and lessons learned while transitioning from the emergency shelter setting. The findings indicate that survivors transitioning out of DV shelters face a multitude of risks, challenges, and stressors. Our findings invite researchers and practitioners to further examine best practices that support families transitioning from shelter.